[PP.01.04] USING TELEMONITORED HOME BLOOD PRESSURE MEASUREMENT TO ASSESS THE TRUE PREVALENCE OF HYPERTENSION IN SINGAPORE. (September 2016) - Mondry, A.; Tan, G.; Ooi, V.
Abstract : Objective: Hypertension is common in Singapore, with published prevalence rates based on office blood pressure measurements. Many patients referred to specialist hypertension services are normotensive on further evaluation. Inappropriate referrals block resources that could be targeted more appropriately. As part of a community outreach program, Ng Teng Fong General Hospital of Jurong Health Services conducts regular population health screenings which include blood pressure (BP) measurements. Participants with BP > 140/90 mmHg are advised to visit primary care services. This study aims at assessing how many of these are truly hypertensive. Design and method: In ongoing population health screenings, targeting 2950 participants from Western Singapore annually, BP is measured on registration. Patients with two consecutive measurements between 140/90–180/110 mmHg are offered participation in our study. They receive a Bluetooth enabled BP monitor and instructions on how and when to record their BP at home. Seven day averages are calculated, and diagnosis of hypertension is based on these values. Patients receive written health advice based on the telemonitored BP and their basic risk factors. They are further offered a complementary visit to a primary care provider who is aware of the telemonitored assessment. Results: Since October 2015, 816 residents attended the health screening. Full data for 626 are available for preliminary reporting. 69 (11%) had elevated BP values at registration; 23 participated in our study. Of these, 7 (30%) were normotensive. One patient with repeated BP measurements exceeding 180 mmHg was identified by telemonitoring and urgently referred to primary care services, where her BP was controlled before the end of the telemonitoring period. Figure. No caption available. Conclusions: Amongst the participants of the community health screenings in Western Singapore, prevalence of hypertension at registration is significantly lower than the published rates. When diagnosis of hypertension is based on telemonitored home measurements, the prevalence drops by a further 30%. The data presented in this abstract are preliminary but show a clear and internally consistent trend towards lower BP prevalence in the resident population. We conclude that published data may not reflect true prevalence rates of hypertension in Singapore.